MANAJEMEN PUSAT KEGIATAN BELAJAR MASYARAKAT DALAM PEMERATAAN PENDIDIKAN MELALUI PAKET C - Wahyuni, Lisa Gusdil; Meditamar, Muhd Odha (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study examines the management of the Istiqomah Pendung Tengah Community Learning Center (PKBM) in promoting educational equity through the Paket C program. A qualitative-descriptive approach was employed, with data collected through in-depth interviews, observation, and documentation involving the PKBM head, administrators, tutors, and learners. The study focused on five key management aspects: planning, organizing, implementation, supervision, and evaluation. The results indicate that all management stages have been carried out systematically and participatively. Planning involved all stakeholders according to learners’ needs; organizing implemented clear task distribution despite human resource limitations; learning activities were conducted flexibly using active, contextual, and Problem-Based Learning methods; supervision was carried out internally and externally to ensure quality; and both program and learning evaluations were conducted periodically to improve educational outcomes. Supporting factors included community and government support, institutional accreditation, and a strategic location, while main challenges involved low learner attendance, limited funding, and inadequate facilities.